The woman question - Evans, Mary 1946- (London SAGE Publications, 1994)
Revised and updated edition, to reflect the transformation of women's studies over the last decade. Topics covered include contemporary feminism, the construction of the "feminine", and "femininity", and the ways in which femininity and masculinity are treated in language and the visual arts.
Feminism, humanism and postmodernism / Kate Soper -- A horror of Isms / Madhu Kishwar -- Age, race, class and sex: women redefining difference / Audre Lorde -- Femininity and its discontents / Jacqueline Rose -- Creating the sexual future / Sheila Jeffreys -- Recovering women in history from feminist deconstructionism / Liz Stanley -- The social construction of black feminist thought / Patricia Hill Collins -- Feminism and theories of scientific knowledge / Sandra Harding -- Sex and death in the rational world of defense intellectuals / Carol Cohn -- She's gotta have it: the representation of black female sexuality on film / Felly Nkweto Simmonds -- Reading Buchi Emecheta: contests for women's experience in women's studies / Donna Haraway -- Feminism and culture, the movie: a critical overview of writing on women and cinema / Maria Lauret -- Women's unwaged work: the heart of the informal sector / Selma James -- Sex and race in the labour market / Irene Bruegel -- Out but not down: Lesbians' experience of housing / Jayne Egerton -- Narrow definitions of culture: the case of early motherhood / Ann Phoenix -- The sexual contract: the end of the story? / Carole Pateman -- Toward feminist jurisprudence / Catharine MacKinnon -- Pornography / Andrea Dworkin -- Theory into practice: the problem of pornography / Carol Smart -- Women, rape and law reform / Jennifer Temkin -- The 'Woman question' in the age of communism's collapse / Maxine Molyneux -- Transforming socialist-feminism: the challenge of racism / Kum-Kum Bhavnani and Margaret Coulson -- There's no place like home: on the place of identity in feminist politics / Mary Louis Adams -- False promises: anti-pornography feminism / Lynne Segal -- The master's tools will never dismantle the master's house / Audre Lorde.
Includes bibliographical references (pages [369]-373) and index.
Keywords: Feminism -- History; Sex role -- History; Discrimination against women -- History